The impact of the internal work environment on maintaining health competencies: An applied study on Tarif General Hospital - Alrouili, Mohammad Awijan (Journal of Economic, Administrative and Legal Sciences, 2019)
The present study aimed at identifying the impact of the internal work environment on retaining the health competencies at Tarif General Hospital in Saudi Arabia. Specifically, this study aimed to identify post-work conditions, after compensation, after relationship with co-workers, after professional growth and retention of health competencies in the study sample. Based on the literature review conducted by the researcher, the competencies in the health institutions in the Kingdom of Saudi Arabia are facing a number of challenges that have a significant impact on their continued work, which are affected by the internal dimensions of the work affected by the ability of the institution to retain health competencies, Which called for researcher to study the dimensions of internal work conditions in the hospital Tarif general and impact on the retention of competencies. In order to measure this, the researcher formulated four hypotheses that aimed at measuring the statistical relationship between the variables of the study. It was assumed that there is a statistically significant relationship between working conditions and retention of health competencies at Tarif General Hospital. There is a statistically significant relation between compensation and retention of health competencies in Tarif General Hospital. There is a statistically significant relation between the relationship with colleagues and management and retention of health competencies at Tarif General Hospital and the existence of a statistically significant relationship between the professional growth and retention of health competencies at Tarif General Hospital. The importance of this study stems from the fact that it deals with a very important subject, which is the internal work environment of Tarif General Hospital. In addition, the importance of this study stems from the fact that it aims to improve the health work and its quality. In order to achieve the study goals, the researcher used the descriptive analytical approach. The researcher used the questionnaire as the study tool. The study population comprised all the medical staff at Turaif General Hospital. Questionnaires were distributed to the entire study sample that consisted of (220) individuals. The number of questionnaires valid for study was (183) questionnaires. The research findings were as follows: the participants’ estimate of the work circumstances dimension was high (3.64), the participants’ estimate of the compensation dimension was moderate (3.32), the participants’ estimate of the relationship with colleagues dimension was high (3.62), the participants’ estimate of the professional growth dimension was weak (2.39), and the participants’ estimate of medical competencies retenion level was intermediate (2.75). Accordingly, the researcher’s major recommendations are: the need to create the right atmosphere for personnel in hospitals, the interest of the hospital to provide the appropriate conditions for the staff in terms of the physical and moral aspects for building the work adjustment in the staff, and conducting training courses and educational lectures for personnel in hospitals on how to cope with the work pressures.